The Great Recession’s biggest losers: The euro area’s jobless - Kilhoffer, Zachary; Beblavy, Miroslav (Brussels, 2017)
"The euro area continues to recover from the Great Recession, with several recent publications offering optimistic assessments of the euro area’s economic performance. The European Commission’s “Employment and Social Developments in Europe 2017” report, for example, praises moderate economic growth and “solid net job creation” in a “job-rich recovery”. While the European Commission acknowledged ongoing challenges such as youth unemployment, it must also be recognised that the euro area’s recovery has been piecemeal. Economic growth is encouraging, but it obscures the unemployed millions who have not tasted the fruits of the recovery. The euro area’s labour market, while posting gains, remains in a worse state than before the Great Recession. Nearly half of the unemployed in the euro area have been jobless for over a year. In contrast with the United States, Japan and other regions hit hard by the crisis, the euro area’s labour market exemplifies the most enduring damage of the Great Recession. This CEPS Policy Insight argues that European lawmakers need to soberly acknowledge the job market’s failures and take targeted action, addressing the regions and demographics for whom the recovery is not working."